2022
DOI: 10.32678/jsga.v9i01.5942
|View full text |Cite
|
Sign up to set email alerts
|

Upaya Pelestarian Lingkungan Melalui Penguatan Ekologi Keluarga Berbasis Al-Quran

Abstract: Pollution and environmental damage are an unavoidable phenomenon nowadays. The Forum for the Environment (WALHI) noted that the earth's temperature is currently increasing by 1.1 degrees Celsius, carbon dioxide emissions are also increasing, forests are decreasing due to the large number of mining areas and oil palm plantations. According to the 2018 Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES), Indonesia continues to lose 650 thousand hectares of forest every year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This is due to a loss of tolerance, the results of a survey by the Indonesian Survey Circle found that as many as 31% of youth were intolerant (Etikasari, 2018). in Indonesia, starting from floods, tornadoes, landslides, forest and land fires, droughts, and heat waves (Febriani, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to a loss of tolerance, the results of a survey by the Indonesian Survey Circle found that as many as 31% of youth were intolerant (Etikasari, 2018). in Indonesia, starting from floods, tornadoes, landslides, forest and land fires, droughts, and heat waves (Febriani, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to a loss of tolerance, the results of a survey by the Indonesian Survey Circle which found that as many as 31% of youth were intolerant ( (Etikasari, 2018). in Indonesia, starting from floods, tornadoes, landslides, forest and land fires, droughts, and heat waves (Febriani, 2022).…”
Section: Introductionmentioning
confidence: 99%